China's troubled waters : maritime disputes in theoretical perspective - Chan, Steve (Cambridge : Cambridge University Press, 2016)
How are China's ongoing sovereignty disputes in the East and South China Seas likely to evolve? Are relations across the Taiwan Strait poised to enter a new period of relaxation or tension? How are economic interdependence, domestic public opinion, and the deterrence role played by the US likely to affect China's relations with its counterparts in these disputes? Although territorial disputes have been the leading cause for interstate wars in the past, China has settled most of its land borders with its neighbours. Its maritime boundaries, however, have remained contentious. This book examines China's conduct in these maritime disputes in order to analyse Beijing's foreign policy intentions in general. Rather than studying Chinese motives in isolation, Steve Chan uses recent theoretical and empirical insights from international relations research to analyse China's management of its maritime disputes.
Machine generated contents note: 1. Embedding China's maritime disputes in general IR research; 2. Territorial conflicts: mitigating and aggravating circumstances; 3. Trust, reassurance, and credible commitment; 4. Deterrence theories: bringing in the United States; 5. Taiwan's two-level interactions with China; 6. Multilateralism in the East and South China Sea disputes; 7. Conclusion.
Title from publisher's bibliographic system (viewed on 05 Feb 2016).
Keywords: China -- Boundaries; Maritime boundaries -- China; China -- Foreign relations -- Southeast Asia; Southeast Asia -- Foreign relations -- China; East China Sea -- Strategic aspects; East China Sea -- International status; South China Sea -- Strategic aspects; South China Sea -- International status